Social Contracts: Pillars of Community Conservation Partnerships in Lore Lindu National Park, Indonesia - Ice Anugrahsari; Mustofa Agung Sardjono; Nur Fitriyah; Golar Golar (Forest and Society, 2020)
The Community Conservation Partnership Agreement (KKM) was an effort to reduce, prevent and mitigate the impacts arising from the complexity of managing Lore Lindu National Park. Several approaches in building KKM in the National Park had been carried out by several parties but had not proceeded as expected. Social Contracts were built to advance community agreements. The purpose of this study was to explore the obstacles and strategies for implementing KKM in the National Park. A qualitative approach was used in this study, through in-depth interviews, field observations, and active research in the process of drafting the KKM agreement. The results showed there were multiple interpretations of the roles, functions, and work of the parties based on their authority and interests in building the KKM. This resulted in the KKM becoming unsustainable. Findings show that in order to re-establish the KKM requires strategic steps, which mediate across stakeholder interests. Partnerships towards effective social contracts would only succeed if there was recognition of, and meaningful involvement among parties that begin at the design and planning processes and continue throughout the implementation phases of the partnership activities. The process of building a social contract must therefore begin with solid communication between stakeholders, which establish institutional mechanisms that are systematic, promote active coordinative, and are based on the trust and understanding between stakeholders.